EFEKTIFITAS HANDOUT BERGAMBAR DILENGKAPI PETA KONSEP PADA MATERI SISTEM REPRODUKSI MANUSIA KELAS XI SEMESTER II TAHUN PELAJARAN 2013/2014 - Ramadani, Sari - (STKIP PGRI Sumbar, 2014)
The background of this research are the lack of action and motivation of the students in learning process, so the result of the biology study still under average. This problem happen because the lack of motivation and understanding about human reproduction. The lack of understanding about the structure, fuction, process and also the pain that will be explained in the pictures. Bases on that problems, the writer use the picture handout media that has completed with the map of concept that will be hoped can increase the action, motivation and the result of the study. The aim of this research is to know the effectivity of the picture handout media that has completed with the map of concept that have developed before in human system reproduction materi toward the activity, motivation, and the result of the study of students XI IPA2 semester II SMA Kartika I-5 Padang year 2013/2014. The kind of this research is the development. The population it this research are the students of XI IPA2 totaling 41 students. This research is done on April-May 2014. The design of this research is before-after. Based on the analysis that is got the result in pretest is 34,96, the average score in 70,29. Based on the percentage of completeness acore of the study 75,61%. And based in test-t the score is 16,53. From the analysis of the data that has been acquired after to the statistical tes and the tes effectifity can be concluded that use the picture handout media that has completed with the map of concept effective because it can increase activity, motivation, and result of the study of students XI IPA2 semester II SMA Kartika I-5 Padang year 2013/2014.